Analysis of a gene cluster for sarcotoxin II, a group of antibacterial proteins of Sarcophaga peregrina. - Kanai, A (1990)
Sarcotoxin II is a group of antibacterial proteins of Sarcophaga peregrina (flesh fly) with related primary structures. We have cloned three genes in this family. These genes formed a tandem array with about 2-kb intervals, and one of them was present in the opposite strand. The putative amino acid sequences of the proteins encoded by these genes were very similar except for a deletion in one of them. All of the genes were found to be activated transiently in the same way when the larval body wall was injured, suggesting that the encoded proteins are acute-phase-responsive proteins for protecting the insect from bacterial infection.